Plant density in maize open-pollinated varieties (Revista de Ciências Agroveterinárias, 2007)
Information about the plant density that optimizes grain yield of maize open-pollinated varieties (OPV), especially in agro-ecological systems, is reduced. The aim of this work was to evaluate the effect of plant density on maize OPV yield. Two experiments were conducted in Papanduva, SC, Brazil, during the growing seasons of 2004/05 and 2005/06. Treatments were arranged in a completely randomized design, using a factorial scheme (4x4), with three replicates. Four maize genotypes were evaluated, three OPV (SCS 153-Esperança, MPA 01 and Pixurum 06); and one hybrid (AS-1544 in the first season and AS- 3601 in the second season). These genotypes were grown in four plant densities: 25,000; 40,000; 55,000; and 70,000 plants ha-1. Plant height, stalk diameter, plant lodging and stalk breakage, grain yield and its components (ears number per plant, grains number per ear and grain mass) were evaluated. The plant densities that optimized maize OPV grain yield ranged from 45,000 to 55,000 plants ha-1.
Keywords: competition; yield; yield components.